ENTREPRENEURSHIP KNOWLEDGE AND LOCUS OF CONTROL IN INCREASING INTEREST IN ENTREPRENEURSHIP - Ina Ratnamiasih; Dewi Rohmah (Jurnal Riset Bisnis dan Manajemen, 2023)
This study aims to determine the effect of entrepreneurial knowledge and locus of control on student interest in entrepreneurship. The research method used is a quantitative method with data collection using a questionnaire on a sample of 291 students. The data analysis technique used multiple linear regression and multiple correction. To test the hypothesis and the coefficient of determination using the SPSS 26 program. The results showed that the influence of entrepreneurial knowledge had an effect of 23% while the locus of control was 55.5% on student interest in entrepreneurship. The total influence of entrepreneurial knowledge and locus of control on entrepreneurial interest is 78.5%. The results of this study reinforce the importance of the higher education curriculum in paying attention to entrepreneurial knowledge and increasing student locus of control to increase student interest in entrepreneurship